America's "failing" schools : how parents and teachers can cope with No Child Left Behind - Popham, W. James (RoutledgeFalmer, 2004)
'No Child Left' Behind, signed into law by President Bush in January 2002, is the most significant education legislation in decades. It calls for substantially expanded student testing, more stringent accountability requirements, and annual school-focused report cards at the state, district, and school levels. Despite the fact that it affects schooling at every possible level, few people understand its implications or reach. In America's 'Failing' Schools, Popham sets the record straight for teachers, students, and parents alike. In clear, accessible language the book explains the relevant.